The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10142-016-0503-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the evolution, expression, and cis-regulatory element of polygalacturonase genes in grasses and dicots

Abstract: Cell walls are a distinguishing characteristic of plants essential to their survival. The pectin content of primary cell walls in grasses and dicots is distinctly different. Polygalacturonases (PGs) can degrade pectins and participate in multiple developmental processes of plants. This study comprehensively compared the evolution, expression, and cis-regulatory element of PGs in grasses and dicots. A total of 577 PGs identified from five grasses and five dicots fell into seven clades. Evolutionary analysis dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Domains I and II may constitute catalytic sites, domain III may participate in the reaction, and domain IV constitutes a possible candidate for the interaction with the ionic groups of the carboxylic acid groups in the substrate [9]. Domain III shows lower conservation and is missing in PGs belonging to clade E, and a PG gene can be identified as containing at least one of the four conserved domains [7,8,9,29]. Of the 54 PGs, 40 contained four conserved domains (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Domains I and II may constitute catalytic sites, domain III may participate in the reaction, and domain IV constitutes a possible candidate for the interaction with the ionic groups of the carboxylic acid groups in the substrate [9]. Domain III shows lower conservation and is missing in PGs belonging to clade E, and a PG gene can be identified as containing at least one of the four conserved domains [7,8,9,29]. Of the 54 PGs, 40 contained four conserved domains (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In B. rapa and C. sativus , most BrPG and CsPG genes in Clade E were found to be ubiquitously expressed in different tissues [8,12]. Expression patterns of PG genes in the other two dicots ( Glycine max and Medicago truncatula ) and two grasses ( Zea mays and O. sativa ) also showed that most of the clade E members could be detected at high overall expression levels in all tissues [7]. In accordance with previous research, we found that more than half SlPGs of Group I belonged to Clade E and were also defined as being expressed ubiquitously (Figure 4, Table S3) which further proved the previous theory that the Clade E members of PG family are possibly ancient proteins and are fundamental and indispensable in almost all plant organs of different species [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations